Gambaran Pengetahuan Perawat Poliklinik dan IGD terhadap Penyakit Parkinson - Adhanisa Hamdani, Ismi; Felix, Felix (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: Early detection and prompt treatment in Parkinson’s Disease (PD) can improve patients’ quality of life. The complexity of PD requires multidisciplinary team management. Nurses play roles in explaining nursing diagnosis and interventions such as motor function and fall risk, dysautonomia, disorder of communication and sleep, adherence to treatment, and advance stage PD treatment. Aim: To find out the description of the knowledge of outpatient and emergency department nurses regarding Parkinson's Disease at Ciawi Regional General Hospital. Methods: Observational descriptive study with a cross-sectional design using a questionnaire that has been tested for validity and reliability. Results: The majority of respondents are aged 30-40 years (60.4%), with educational level Diploma-3 (78.2%). About half of them have interacted with patients with PD (56.4%), but most of them have never received education about PD (62.4%). Majority level of knowledge about PD is sufficient (40.6%). The level of sufficient knowledge was obtained from respondents with educational level Diploma-3, aged 30-40 years, work experience > 10 years, and have interaction with patients with PD. Discussion: The level of knowledge of nurses at Ciawi Regional Hospital was mostly at 41 (40.6%), followed by a good level of knowledge at 32 (31.7%), and less at 28 (27.7%). This study is the first in Indonesia, and shows the need to increase the knowledge of PD among nurses as part of a multidisciplinary team. Education programs may have roles in increasing the level of knowledge regarding PD. Keywords: Knowledge, Multidisciplinary, Nurse, Parkinson’s Disease.